Customised Vaginal Stent - The Phases in Management of Vaginal Agenesis in Mayer-Rokitansky-Küster-Hauser (MRKH) Syndrome - Fathima Banu Raza; Kapil Raju; Annapoorani Babu; Anand Kumar Vaidyanathan; Bhavna S Mehta (Tehran University of Medical Sciences, 2023)
Objective: Vaginal agenesis or atresia in females suffering from MRKH syndrome is more common and management involves both surgical and non-surgical approaches. Use of prefabricated stents to maintain the patency of the canal may not fit appropriately during the initial surgical phase and are not economical. This case report discusses a series of modifications in a custom-made vaginal dilator to improve the retention for expansion after surgical management of MRKH syndrome. Case report: A 28-year-old female diagnosed with MRKH syndrome with characteristic Mullerian agenesis was referred for customised vaginal stent. Customised surgical stent was fabricated with loops for orientation and retention, which was later modified into interim expansion and passive stent. Conclusion: The customisation of the vaginal stent, provision of a retentive loop that positioned the stent in the proper orientation, and gradual increase in the size of the stent, ensured dilatation in a patient with vaginal agenesis.